CRIMINAL LIABILITY OF CHILDREN IN NARCOTICS CRIMES UNDER THE JUVENILE CRIMINAL JUSTICE SYSTEM - Andi Khaedhir Kamri (CV. RADJA PUBLIKA, 2025)
This study discusses juvenile criminal liability for narcotics crimes in the context of the juvenile criminal justice system in Indonesia. In recent years, narcotics abuse among children and adolescents has increased significantly, making this issue a serious challenge for society and the government. Through a normative approach and juridical analysis, this study explores the basic principles that govern child protection, as well as the challenges faced in the implementation of the juvenile criminal justice system. The findings suggest that social, economic, and psychological factors contribute to drug abuse among children. The study also highlights the importance of rehabilitation as the main approach in dealing with narcotics abuse cases, compared to repressive law enforcement. In addition, an evaluation of existing policies and practices is needed to ensure that children's rights are protected and that they have the opportunity for social reintegration. The conclusions of this study emphasize the need for collaboration between governments, communities, and non-governmental organizations to create an environment that supports the recovery of children involved in narcotics abuse. Further research is needed to explore more effective and sustainable solutions in addressing this issue. With a more comprehensive approach, it is hoped that children can have a better future and be free from the negative influence of narcotics.